(untitled) (Fisioterapia & Saúde Funcional, 2025)
Objective: To verify the intra and inter reliability of young adults women’s pelvic body composition measurements with the dual x-ray absorptiometry images. Materials and methods: This was a cross-section study of reliability composed by 68 women (35.79 ±14.02 years). Two examiners (Examiner 1 and Examiner 2) performed the measurement from pelvic region through dual energy x-ray absorptiometry (DXA) images. The Examiner 1 performed all the DXA body composition exams. For intra-rater reliability, the Examiner 1 analyzed the image in 2 days separated by 1-week interval. For inter-rater reliability, the Examiner 2 analyzed the images on a different day than Examiner 1. The pelvis was the region of interest (ROI) of this study that was selected manually giving the results from local body mass, lean mass, fat mass, and % fat. Intraclass correlation coefficient (ICC) was calculated considering ICC≥0.75 excellent; 0.40≤ ICC <0.75 satisfactory; and ICC <0.40 poor, with a level significance of 5% and a 95% confidence interval. Results: The intra-rater reliability of Examiner 1 was considered excellent, with ICC above 0.86(p<0.0001). The inter-rater reliability was considering excellent between examiners, with ICC above 0.97(p<0.0001). Conclusion: The intra and inter-rater reliability of Pelvis ROI shows great reliability from pelvic region measurement by DXA images.